Treatment of Labially Impacted Canine, Keys to Successful Outcomes in Periodontal Perspectives - Chen, Ya-Wei; Luk, Tammy; Matsumoto, Kensuke (The Journal of Dentists, 2020)
Maxillary canines are the most commonly impacted teeth following third molars. Considered as the cornerstone of the dental arch, appropriate treatment of these impacted canines should be applied in order to maintain the function and esthetic integrity. Labially impacted canines are not uncommon in Asian countries, and it is often challenging to manage them without the esthetic or periodontal consequences. The apical positioned flap (APF) is one of the periodontal procedures that has been proposed to expose labially impacted canines. The APF technique can provide adequate attached gingiva, good visibility and faster canine retraction during orthodontic treatment; however, it is technique-sensitive. Therefore, in this article, two cases of labially impacted maxillary canines treated with an APF and orthodontic treatment are presented, and the keys to successful treatment outcomes in periodontal perspectives are discussed.